Barrier Factors Affecting Adoption of Green Building Technologies in Nigeria / Ganiyu Amuda-Yusuf ... [et al.] - Ganiyu, Amuda-Yusuf; Adebiyi, Raheem Wasiu Mayowa; Abdulraheem, Ranti Taibat; Orire, Maimunat; Eluwa, Idris Soliu; Stephen, Eyinaya (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Greenhouse gas emission from activities in the built environment is increasing exponentially due to increase in building operations. This study aims at determining factors that affect adoption of Green Building Technologies that normally reduce greenhouse gas emissions. To elicit relevant information, online structured questionnaire forms were administered on practitioners who have been involved in green building development in Nigeria. Mean score ranking was adopted in ranking the barriers to green building technologies, while discriminant analysis was performed to examine how organizations groups (client, consulting, contracting, academia) were distinguished on the barrier factors identified. Findings revealed that, out of the 23 barrier factors considered in this research, lack of institutions to formulate policies and set guidelines (mean score - 4.5) ranked 1st as barrier to adoption of green building technologies in Nigeria. This is closely followed by lack of information about green products (4.0), low level of awareness about sustainability issues (4.0), human resource and client knowledge, lack of knowledge about green building technologies, high cost of green products, while unavailability of sustainable materials and products ranked the lowest (2.7). Only nine factors at 0.05 level of significance entered the discriminant analysis model and emerged as variables with the most significant power in differentiating the organization groupings on the basis of perceived barriers to adoption of green building technologies. The study recommends that there should be strong political will from government, to establish institutions that formulate policies on green building technologies.